Pharmacist intervention through protocol-based pharmacotherapy management is effective to ensure safety in invasive procedures for chronic liver disease - Yuuka Shibata; Yuki Koga; Yuki Sato; Emiko Mashida; Tomokazu Kawaoka; Eisuke Murakami; Kei Amioka; Yusuke Johira; Kensuke Naruto; Takanori Taogoshi; Tomoharu Yokooji; Masataka Tsuge; et al. (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background The risk of hemorrhagic complications in patients with chronic liver disease during invasive procedures should be considered. Patients with low platelet counts were administered platelet products prior to procedures based on a physician's judgment. However, there are no standards for allocating the bleeding risk associated with each procedure, platelet counts to avoid these risks, or methods for determining platelet counts. In this study, we evaluated whether pharmacists could reduce the use of platelet products by suggesting thrombopoietin receptor agonists using protocol-based pharmacotherapy management to assess procedural bleeding risk and platelet counts. Methods Among patients with chronic liver disease who were scheduled to undergo invasive procedures between August 2022 and February 2023, those who were interviewed by a pharmacist prior to the procedures were defined as the intervention group (n = 80) and the others as the non-intervention group (n = 224). The protocol was to define the procedural bleeding risk and platelet count. Pharmacists suggested prescribing a thrombopoietin receptor agonist to patients with platelet counts below the recommended counts. Results The use of platelet products and thrombopoietin receptor agonists was 0% and 7.5% and 3.1% and 0% in the intervention and non-intervention groups, respectively. Among the patients who were required to receive lusutrombopag, all patients in the intervention groups did not receive platelet product but lusutrombopag alone. However, the rates of patients with the recommended platelet count were not different between the intervention and non-intervention groups. Conclusions The use of platelet products decreases without the increased incidences of hemorrhage if pharmacists suggest prescribing thrombopoietin receptor agonists based on their assessment of the platelet count and the bleeding risk of the procedure.